Effect of Pelvic Muscle Exercise on Sexual Satisfaction among Primiparous Women - Maryam Modarres; Fatemeh Rahimikian; Elaheh Booriaie (Tehran University of Medical Sciences, 2013)
Background & Aim: Most of the psychological turmoil of marital conflicts is related to sexual dissatisfaction. Sexual satisfaction is influenced by physical and mental illnesses. Pelvic floor muscle relaxation is a major health problem in which prolapsed pelvic floor muscles causes paralysis, pelvic organs&apos prolpases, pelvic organs&apos dysfunction, dyspareunia, and back pain. The aim of this study was to assess the effect of pelvic floor muscle exercise on sexual satisfaction in primiparous women. Methods & Materials: This clinical trial was conducted among 100 primiparous women selected through cluster randomized sampling from five clinics of Tehran University of Medical Sciences. Samples were randomly divided into two equal groups. The intervention group received pelvic floor exercises (Kegel) for 16 weeks. The control group did not receive any intervention. Data were collected using the Linda Berg questionnaire before the intervention and 16 weeks after the intervention in both groups. Data were analyzed using descriptive statistics and chi-square, t-test in the SPSS v.18. Results: After 16 weeks, significant differences were reported in the levels of sexual satisfaction in the intervention and control groups (P<0.001). Conclusion: The Kegel exercises are easy and non-expensive methods that should be offered by health professionals to increase sexual satisfaction in women after childbirth.